The effect of indigestible dextrin and phytosterol on serum LDL-cholesterol level on hypercholesterolemic subjects (Faculty of Medicine Universitas Indonesia, 2009)
Aim To investigate the effects of indigestible dextrin 2x2.3g/day and phytosterol 2x0.6g/day provided for 6 weeks in lowering serum LDL-cholesterol levels amongs hypercholesterolemic subjects. Methods A randomized clinical trial, two pararel groups, double blinded and randomly assigned to each different group was done in 16 subjects per-group. Results Before the, intervention the level of LDL cholesterol of both ID and FS group were 158.81 ± 17.74 mg/dL and 176.18 ± 25.31 mg/dL, respectively. After the intervention there was a significant reduction in LDL cholesterol level in both groups, i.e. among the ID group by 20.93 ± 12.65 mg/dL (13.24%) with p value of <0.001, while the reduction of LDL cholesterol level among the PS group was 21.87 ± 28.76 mg/dL (11.21%) with p value of 0.008. However, the reduction of cholesterol level between the two groups did not show any significant difference. Conclusion Consuming indigestible dextrin 2x2.3g/day and 2x0.6g/day phytosterol (PS) for 6 weeks will have the same ability to decrease the serum cholesterol level in hypercholesterolemic subjects. (Med J Indones 2009; 18: 114-9) Key words: indigestible dextrin, phytosterol, cholesterol